Type I tympanoplasty in pediatric age – The results of a tertiary hospital. (November 2021) - Gonçalves, Ana Isabel; Rato, Catarina; Duarte, Delfim; de Vilhena, Ditza
Abstract: Introduction: The performance of pediatric tympanoplasty is a matter of controversy in the literature, varying from 35 to 94%. Several authors argue that the performance of tympanoplasty should be delayed until 6–8 years old or even after 10 years old. Objectives: To analyze the results of type I tympanoplasty in pediatric age and to identify possible prognostic factors. Material and methods: Retrospective study of children undergoing type I tympanoplasty (Portmann's classification) between January 2012 and December 2018 in our hospital. The following variables were analyzed: age, gender, etiology, size and location of the perforation, operated ear, season of the surgery, experience of the surgeon, condition of the contralateral ear, previous otologic surgery, previous adenoidectomy, presence of tympanosclerosis, surgical approach, type of graft, tympanoplasty technique, pre and postoperative audiometric results and follow-up time. The integrity of tympanic membrane (TM) was defined as anatomical success at 6 months postoperatively and as functional success we defined a pure tone average < 20 dB (mean of 0.5–4 KHz) in postoperative tonal audiometry, performed between 3 and 6 months after surgery. Results: A total of 48 ears operated on 38 patients, aged between 8 and 17 years. Anatomical and functional success rates of 81.3% and 87.5%, respectively, were obtained. The only statistically significant poor prognostic factor was the presence of tympanosclerosis plaques in the middle ear, negatively affecting anatomical success (p = 0.007) and functional success (p = 0.008). There was an anatomical failure rate of 25% in the anterior and lower TM perforations, 14.3% in central and 7.7% in posterior perforations (p = 0.603). Perforations >50% of the TM surface showed a functional failure rate of 25% vs. 10% in perforations <50% of the TM (p = 0.242) and anatomical failure rates of 12.5% vs. 20%, respectively (p = 0.620). Regarding age, the group <12 years had an anatomical success rate of 85.7%, while the group ≥12 years had a rate of 79.4% (p = 0.611). As for the functional success rates, this was 92.9% and 85.3%, respectively (p = 0.471). Apart from the presence of tympanosclerosis, no other variable was statistically significantly associated with surgical success. Conclusions: Our study shows that type I tympanoplasty in pediatric age is a procedure with a high rate of anatomical and functional success. The presence of tympanosclerosis plaques in the middle ear was the only factor associated with poor anatomical and functional prognosis. Contrary to what has been described in some articles in the literature, in this study, the functional and anatomical success rates did not vary according to the age group.